Development of Financial Management Information System Based IoT Integrated Using Waterfall Model - Amalia Nuril Hidayati; Nadia Roosmalita Sari (SMATIKA JURNAL : STIKI Informatika Jurnal, 2025)
Financial management is a core subject of the study program that must be mastered by students of the Sharia Financial Management study program. This course presents material about financial management in theory. Based on the results of initial observations that have been made, Sharia Financial Management students have not even tried to directly practice financial management using an information system in managing finances. This happens because several existing financial management information systems are closed systems so students cannot access the system. Therefore, this study proposes a financial management information system with the support of IoT technology as a simulation or practice medium for Sharia Financial Management study program students. The proposed method in this study uses Waterfall model. Based on the average value of TAM analysis, it is 81.72%, where this value is included in the Very Good for use to strengthen the Financial Literacy of Sharia Financial Management students.